2015
DOI: 10.1179/1743284715y.0000000052
|View full text |Cite
|
Sign up to set email alerts
|

Wetting behaviour of Cu based alloys on spinel substrates in pyrometallurgical context

Abstract: Metal droplet losses in slags are an important issue in copper industry. One significant aspect that promotes the entrainment of metal droplets in the slag is their attachment to spinel solids. In the present study, the wetting behaviour of copper alloys on spinel substrates has been investigated in the presence and absence of a slag phase. At first, the attachment was investigated using a synthetic slag containing spinel particles. Microstructural analysis of quenched slag reveals the presence of microdroplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
3
27
1
Order By: Relevance
“…[12] There exists, however, an important additional source of mechanically entrained droplets which have been omitted in most studies: the attachment of droplets to solids in slags, hampering the sedimentation. This observation was reported by Ip and Toguri [9] and Andrews, [11] and demonstrated for a synthetic slag system by De Wilde et al [13] These solids are often found to have a spinel structure. Even though the copper attachment to solid spinels was clearly observed, [13] limited experimental or industrial data and fundamental insights concerning the active mechanisms are available.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…[12] There exists, however, an important additional source of mechanically entrained droplets which have been omitted in most studies: the attachment of droplets to solids in slags, hampering the sedimentation. This observation was reported by Ip and Toguri [9] and Andrews, [11] and demonstrated for a synthetic slag system by De Wilde et al [13] These solids are often found to have a spinel structure. Even though the copper attachment to solid spinels was clearly observed, [13] limited experimental or industrial data and fundamental insights concerning the active mechanisms are available.…”
Section: Introductionsupporting
confidence: 65%
“…This observation was reported by Ip and Toguri [9] and Andrews, [11] and demonstrated for a synthetic slag system by De Wilde et al [13] These solids are often found to have a spinel structure. Even though the copper attachment to solid spinels was clearly observed, [13] limited experimental or industrial data and fundamental insights concerning the active mechanisms are available.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, a perfect phase separation is virtually impossible in practice and valuable metals are lost or reprocessing is required. Insufficient phase separation can originate from mechanical entrainment of metallic droplets, of which the attachment to solid particles in slags is one of the possible reasons, as illustrated in Figure 1 [1]. This attachment creates production losses in industrial Cu smelters [2,3], Pb reduction melting furnaces [4] but also in other industries [5].…”
Section: Introductionmentioning
confidence: 99%